Tensile Strength of Coconut Coir Fiber Composite as an Alternative Material to Replace Fiberglass in Hard Socket - Nur Rachmat; Atika Febri Anggriani; Ahmad Hisyam; Doddy Suprayogi (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Physically disabled is someone who has a movement system disorder or has physical abnormalities such as amputation, withering, stiffness, and others. The self-confidence of someone who has an amputee can be improved by having a prosthesis made, because it can replace the anatomical and functional functions of the body. The socket on the prosthesis is the most important component, because the use of the socket on the prosthesis is directly related to the patient's stump. One of the materials for making socket prosthesis is fiberglass. However, the use of fiberglass has a negative effect, namely it produces gas and dust emissions that can irritate stumps, is not a local product, and is difficult to recycle. Alternative fiber materials are using fibers from nature, coco fiber is an option as an alternative to fiberglass. The tensile strength test is the most basic test. The tensile strength test was carried out to determine the stress, strain, and elastic modulus of the fibrous polymer composites. The purpose of this study was to analyze and compare the tensile strength between fiberglass and coconut coir fiber, so as to find out which fiber material is suitable as an alternative to fiberglass in the manufacture of socket prosthesis. Using experimental quantitative methods. The composite material uses coconut coir fiber which was previously treated with 5% NaOH for 1 hour and then dried for 2-3 days. In the fabrication process using the vacuum bag method. Standard specimen refers to ASTM D3039/3039M. Tensile testing showed that the average tensile strength value of the coco fiber composite was 16.2 MPa and the average tensile strength value of the fiberglass composite was 30.2 MPa. This means that the value of the tensile strength of coco fiber is still below fiberglass and cannot be used as a substitute for fiberglass. However, coconut coir fiber can be used as an alternative to fiberglass, judging from the average maximum force that the coco fiber composite can withstand, which is 2630 N or equivalent to a load of 263 kg, this value is sufficient for the average adult weight in Indonesia with an average weight of 60 kg body